Validated model of platelet slip at stenosis and device surfaces. (2nd April 2020) - Denardo, Scott J.; Denardo, Bruce C.; Carpinone, Paul L.; Dean, William T.; New, David M.; Estrada, Luis E.; Green, Cynthia L.; Yock, Paul G.; Karunasiri, Gamani
Abstract: Platelets are central to thrombosis. However, it is unknown whether platelets slip at vascular or device surfaces. The presence of platelet slip at a surface would interrupt physical contact between the platelet and that surface, and therefore diminish adhesion and thrombosis. Unfortunately, no existing technology can directly measure platelet slip in a biological environment. The objective of this study was to explore whether microspheres–modeling platelets–slip at different vascular and device surfaces in an acrylic scaled-up model coronary artery. The microspheres (3.12 µm diameter) were suspended in a transparent glycerol/water experimental fluid, which flowed continuously at Reynolds numbers typical of coronary flow (200–400) through the model artery. We placed a series of axisymmetric acrylic stenoses (cross-sectional area reduction [CSAr], 20–90%) into the model artery, both without and with a central cylinder present (modeling a percutaneous interventional guide wire, and with a scaled-up Doppler catheter mounted upstream). We used laser Doppler velocimetry (LDV) to measure microsphere velocities within, proximal and distal to each stenosis, and compared to computer simulations of fluid flow with no-slip. For validation, we replaced the acrylic with paraffin stenoses (more biologically relevant from a surface roughness perspective) and then analyzed the signal recorded by the scaled-up Doppler catheter. Using the LDV, we identified progressive microsphere slip proportional to CSAr inside entrances for stenoses ≥60% and ≥40% without and with cylinder present, respectively. Additionally, microsphere slip occurred universally along the cylinder surface. Computer simulations indicated increased fluid shear rates (velocity gradients) at these particular locations, and logistic regression analysis comparing microsphere slip with fluid shear rate resulted in a c-index of 0.989 at a cut-point fluid shear rate of (10.61 [cm −1 ]×mean velocity [cm×sec −1 ]). Moreover, the presence of the cylinder caused disordering of microsphere shear rates distal to higher grade stenoses, indicating a disturbance in their flow. Finally, despite lower precision, the signal recorded by the scaled-up Doppler catheter nonetheless indicated slip at the entry into and at most locations distal to the 90% stenosis. Our validated model establishes proof of concept for platelet slip, and platelet slip explains several important basic and clinical observations. If technological advances allow confirmation in a true biologic environment, then our results will likely influence the development of shear-dependent antiplatelet drugs. Also, adding shear rate information, our results provide a direct experimental fluid dynamic foundation for antiplatelet-focused antithrombotic therapy during coronary interventions directed towards higher grade atherosclerotic stenoses.